Earnings management in the hospitality industry: A systematic literature review - Gonçalves,Beatriz (2024)
Abstract This paper aims to discuss the impact of Earnings Management (EM) practices in the hospitality industry and identify research gaps to be investigated in future research. The methodology is based on a systematic literature review (SLR), including 15 academic papers in the final sample, published from 2004 to 2021. There is clear evidence of EM practices in the hospitality industry, which are implemented through different techniques. Yet, several research gaps still persist. For instance, little is known about the EM behaviour of multinational hotel chains or private Small and Medium-sized Enterprises (SMEs), and we still do not know how such opportunistic behaviour is impacted by different variables. The recent COVID-19 pandemic also offers interesting future research opportunities. Despite the earnings management topic being widely explored in the literature, this SLR shows that the investigation of EM within the hospitality industry is very scarce. Nevertheless, since EM reduces the quality of financial reporting, these practices are a problem for investors, auditors, regulators and other stakeholders, who must rely on earnings disclosure to make decisions, which justifies the importance of its study.